Factors predicting surgical site infection after posterior lumbar surgery: A multicenter retrospective study. Issue 5 (February 2017) - Wang, Tao; Wang, Hui; Yang, Da-Long; Jiang, Li-Qiang; Zhang, Li-Jun; Ding, Wen-Yuan
Abstract : Abstract: This is a retrospective study. The purpose of this study is to explore incidence and risk factors for surgical site infection (SSI) after posterior lumbar surgery. SSI is a common complication after posterior lumbar surgery, bringing mental and physical pain and prolonging hospital stay. However, predisposing factors, as reported less, remain controversial. Patients who underwent posterior lumbar surgery at 3 centers between 2006 and 2016 were included. The possible factors include 3 aspects: demographic variables-age, sex, body mass index (BMI), waist-to-hip radio (WHR), hypertension, diabetes, heart disease, smoking, drinking, steroidal injection, surgical time between June and September, preoperative shower; blood test variables-white blood cell (WBC), neutrophil, red blood cell (RBC), hemoglobin (Hb), total protein (TP), albumin, albumin/globulin (A/G), C-reactive protein (CRP), procalcitonin (PCT), erythrocyte sedimentation rate (ESR) and surgical related variables-operation time, blood loss, operative level, instrumentation, incision length. Factors related with SSI were also performed by multivariate analysis. The prevalence of SSI was 3.00% (267 cases of 8879) had a postoperative wound infection. There were significant difference in WHR (0.92 vs 0.83), WBC (4.31 vs 6.69), TP (58.7 vs 65.2), albumin (36.9 vs 43.2), CRP (2.01 vs 0.57), PCT (0.097 vs 0.067), operation time (217.9 vs 195.7), blood loss (997.1 vs 915.3) and operative level (3.05 vs 2.45) and incision length (24.1 vs 20.0) between SSI group and non-SSI group. >60 years old, female, BMI <18.5 and >30.0, diabetes, male smoking, preoperative steroidal injection, surgical time between June and September, no preoperative shower, instrumentation surgery were risk factors for SSI after posterior lumbar surgery. Many factors, >60 years old, female, BMI, WHR, diabetes, male smoking, preoperative steroidal injection, surgical time between June and September, preoperative shower, WBC, TP, albumin, CRP, PCT, operation time, blood loss and operative level, instrumentation surgery and incision length, could predict SSI after posterior lumbar surgery. Measure should be taken before surgery to lower incidence of SSI after surgery.